Intestinal macrophages - heterogeneity, origins and functions - Mowat, Allan (Henry Stewart Talks, 2012)
Macrophages play essential roles in both homeostasis and inflammation in the intestine, Distinct populations of macrophages control each of these functions, Novel strategies for characterizing mouse intestinal macrophages, A single population of monocyte gives rise to both resident and inflammatory macrophages in intestine, Actions of macrophages in healthy intestine in mice, Actions of macrophages in inflamed intestine in mice, Similar processes in humans, Application of knowledge of macrophages to human diseases including Crohn's disease